VLA4-Enhanced Allogeneic Endothelial Progenitor Cell-Based Therapy Preserves the Aortic Valve Function in a Mouse Model of Dyslipidemia and Diabetes - Alexandru Filippi; Alina Constantin; Nicoleta Alexandru; Cristina Ana Mocanu; Mihaela Loredana Vlad; Ioana Madalina Fenyo; Agneta Simionescu; Dan Teodor Simionescu; Ileana Manduteanu; Adriana Georgescu (MDPI AG, 2022)
The number and function of endothelial progenitor cells (EPCs) are reduced in diabetes, contributing to deteriorated vascular repair and the occurrence of cardiovascular complications. Here, we present the results of treating early diabetic dyslipidemic mice or dyslipidemic with disease-matched EPCs modified to overexpress VLA4 (VLA4-EPCs) as compared with the treatment of EPCs transfected with GFP (GFP-EPCs) as well as EPCs from healthy animals. Organ imaging of injected PKH26-stained cells showed little pulmonary first-pass effects and distribution in highly vascularized organs, with splenic removal from circulation, mostly in non-diabetic animals. Plasma measurements showed pronounced dyslipidemia in all animals and glycaemia indicative of diabetes in streptozotocin-injected animals. Echocardiographic measurements performed 3 days after the treatment showed significantly improved aortic valve function in animals treated with VLA4-overexpressing EPCs compared with GFP-EPCs, and similar results in the groups treated with healthy EPCs and VLA4-EPCs. Immunohistochemical analyses revealed active inflammation and remodelling in all groups but different profiles, with higher MMP9 and lower P-selectin levels in GFP-EPCs, treated animals. In conclusion, our experiments show that genetically modified allogeneic EPCs might be a safe treatment option, with bioavailability in the desired target compartments and the ability to preserve aortic valve function in dyslipidemia and diabetes.